Strengthening Professionalism Madrasah Teachers In Increasing Religious Tolerance (study on madrasah teachers in jakarta and banten region) - Sholichah, Aas Siti; Ningrum, Desy Ayu; Nurbaiti, Nurbaiti (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to determine the strengthening of the professionalism of madrasah teachers and the efforts made by madrasah teachers in increasing religious tolerance. The research method used qualitative research with a field study approach. For data analysis used bservation techniques, interviews and documentation. Strengthening the professionalism of madrasah teachers is carried out by providing personal understanding of the differences in each individual both related to differences in race, ethnicity and religion. Next is to seek information related to religious tolerance through reading materials such as books, magazines, newspapers and related articles. Another strengthening of professionalism was by actively participating in seminars, workshops, training on religious tolerance, both those carried out by the government and non-governmental organizations. The efforts of madrasah teachers in increasing religious tolerance were to provide an understanding to each individual of the differences in various aspects, this aims to get to know each other. Another effort was to give freedom to each individual to carry out worship activities according to religious teachings, by providing facilities that can provide peace and comfort in carrying out worship.